Association of Dietary Calcium Intake With Bone Health and Chronic Diseases: Two Prospective Cohort Studies in China - Guo, Xiaoyu; Gao, Jian; Meng, Xing; Wang, Jiemei; Zhang, Ziwei; Song, Qingrao; Hu, Ke; Sun, Changhao; Li, Ying (Frontiers in Nutrition, 2021)
Calcium is an essential element in our diet and the most abundant mineral in the body. A high proportion of Chinese residents are not meeting dietary calcium recommendations. The purpose of this study was to investigate the relationship between calcium intake and the health of residents in two longitudinal studies of Chinese residents. Methods: This study used nationally representative data from the Harbin Cohort Study on Diet, Nutrition and Chronic Non-communicable Disease Study (HDNNCDS) and China Health Nutrition Survey (CHNS), including 6,499 and 8,140 Chinese adults, respectively, who were free of chronic diseases at recruitment, with mean values of 4.2 and 5.3 years follow-up. Cox’s proportional-hazards regression was conducted to explore the relationship between dietary calcium intake and the incidence of obesity, type 2 diabetes, hypertension, and cardiovascular disease with adjustment for covariates. Results: Calcium intakes were 451.35±203.56 and 484.32±198.61 (mean ± SD) mg/day in HDNNCDS and CHNS. After adjusting the covariates, the relationship between dietary calcium intake and bone mineral density was not statistically significant (p = 0.110). In the multivariate-adjusted Cox proportional-hazards regression model, dietary calcium intakes were inversely associated with obesity incidence in both cohorts (HR [95%CI]: 0.61 [0.48-0.77] and p trend < 0.001 in fixed-effects model), nevertheless, there was no correlation between dietary calcium intake and the risk of type 2 diabetes (p trend = 0.442 and 0.759) and cardiovascular disease (p trend = 0.826 and 0.072). The relationship between dietary calcium intake and the risk of hypertension in the two cohorts was inconsistent (p trend = 0.012 and 0.559). Additionally, after further adjusting the vegetable intake in the original multivariate model, both cohorts found no association between dietary calcium intake and the risk of developing obesity (p trend = 0.084 and 0.444). Conclusions: Our data suggest that the current calcium intake of Chinese residents was inversely associated with obesity, which may be related to consumption of vegetables. Meanwhile, the current calcium intake does not increase the risk of type 2 diabetes, cardiovascular disease, and bone health burden. This research suggested that the Chinese current calcium intake level may have met the needs of the body.